Porous coatings in tube sprayed by electrical explosion and its formation mechanism - LI Wanggen; ZHU Liang; ZHANG Aihua; ZHOU Hui; YANG Zhe (Cailiao gongcheng, 2023)
To produce the porous coating on the inner wall of the pipe is an effective way to enhance heat transfer performance and improve heat exchange efficiency. The electric explosion spraying method was employed to produce the porous coating on the inner wall of the pipe. The surface morphology, roughness and pore distribution of the coating under different initial voltages were studied. The mechanism for the formation of the coating was investigated by the deposition energy and explosive products explained. The results indicate that the initial voltage of the electric explosion spraying influences the microstructure of coating. The optimal porous coating can be obtained when the initial voltage of the electric explosion spraying is 14.0 kV. The optimal porous coating is formed by the accumulation of the small particles. Moreover, the optimal porous coating is obtained, the surface area is 4.47 times that of the uncoated pipe and the porosity of the ideal coating is 57.8%. The uniform round porous coating is formed, when the initial voltage of the electric explosion spraying is 15.2 kV. The porosity of those coating is 40.3%. The formation of the coating depends on the energy deposited on the copper wire during the explosion. The energy deposited on the copper wire acts as the thermodynamic condition for the sprayed particles, determines the energy and particle size of the sprayed particles and the states of the sprayed particles collide with the surface of the base tube or the particles accumulate or form a molten pool. Finally, it influences the microscopic morphology of the coating.